Development of Hydrogen Fuel Cell–Battery Hybrid Multicopter System Thermal Management and Power Management System Based on AMESim - JiHyun Choi; Hyun-Jong Park; Jaeyoung Han (Energies)
Urban Air Mobility (UAM) is gaining attention as a solution to urban population growth and air pollution. Hydrogen fuel cells are applied to overcome the limitations of battery-based UAM, utilizing a PEMFC (Polymer Electrolyte Membrane Fuel Cell) with batteries in a hybrid system to enhance responsiveness. Power management improves efficiency through effective power distribution under varying loads, while thermal management maintains optimal stack temperatures to prevent degradation. This study developed a hydrogen fuel cell–battery hybrid multicopter system using AMESim, consisting of a 138 kW fuel cell stack, 60 kW battery, DC–DC converters, and thrust motors. A rule-based power management system was implemented to define power distribution strategies based on SOC and load demand. The system’s operating range was designed to allocate power according to battery SOC and load variations. For an initial SOC of 45%, the power management system distributed power for flight, and the results showed that the state machine control system reduced hydrogen consumption by 5.85% and parasitic energy by 1.63% compared to the rule-based system.